Turkey’s First Digital Library Management System: IRCICA FARABİ Abdullah - Abdullah Topaloğlu (Türk Kütüphaneciliği)
Digital libraries which are comprised of digitallly concieved materials as well as all sorts of anolog resources which are converted into digital forms, keep, manage, distribute and make available to the public said resources via internet and other mediums. Digital libraries were started to put into use from as early as 1990’s, first in United States of America and in the following years around the world. Efforts, worth note, made for the digitilisation of resources and archiving of digitialised materials began as early as the 2000’s in our country. In this article we would like to delve into details of our work, which can be easily regarded as a first in Turkey, IRCICA FARABI’s philosophy, reason and targets as well as the process of digitilasition.